Does Dietary Intake by Tehranian Adults Align with the 2005 Dietary Guidelines for Americans? Observations from the Tehran Lipid and Glucose Study (Journal of Health, Population and Nutrition, 2011)
The aim of this study was to compare dietary intakes by Tehranian adults with recent dietary guidelines for the Americans. The study made a cross-sectional assessment of the dietary patterns of Tehranian adults using a validated food-frequency questionnaire. It included 2,510 subjects (1,121 men and 1,389 women) aged 19-70 years. They were the participants of the third follow-up survey of the Tehran Lipid and Glucose Study (2005-2008). The dietary patterns were assessed using the latest World Health Organization (WHO)’s nutritional goals and Dietary Guidelines for the Americans Adherence Index (DGAI) 2005. The mean [standard deviation (SD)] DGAI score for this population was 8.31 (1.9). Participants in the highest quartile category of DGAI were more likely to be female, older, non-smoking, and physically active than those in the lowest quartile category (p